2020
DOI: 10.1111/echo.14966
|View full text |Cite|
|
Sign up to set email alerts
|

A pilot study on right ventricular longitudinal strain as a predictor of outcome in COVID‐19 patients with evidence of cardiac involvement

Abstract: Aims The aim of this investigation was to evaluate echocardiographic parameters of cardiac function and in particular right ventricular (RV) function as a predictor of mortality in patients with coronavirus disease‐2019 (COVID‐19) pneumonia. Methods and Results This prospective observational study included 35 patients admitted to a UK district general hospital with COVID‐19 and evidence of cardiac involvement, that is, raised Troponin I levels or clinical evidence of heart failure during the first wave of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…79 In another study of 35 patients, those with RVGLS less than -20% had significantly higher 30 day mortality. 83 RVFAC performed inconsistently in prediction of mortality in COVID-19 patients. In one study that included COVID-19 patients with varying severity, RVFAC was reported to be an independent predictor of mortality.…”
Section: Echocardiographic Predictors Of Mortality In Covid-19mentioning
confidence: 91%
“…79 In another study of 35 patients, those with RVGLS less than -20% had significantly higher 30 day mortality. 83 RVFAC performed inconsistently in prediction of mortality in COVID-19 patients. In one study that included COVID-19 patients with varying severity, RVFAC was reported to be an independent predictor of mortality.…”
Section: Echocardiographic Predictors Of Mortality In Covid-19mentioning
confidence: 91%
“…142,143 In a prospective study of 214 patients with COVID19, measures of RV function and LV function were significantly associated with mortality 164 . Small studies suggest that even subclinical ventricular dysfunction (LV and RV strain by echocardiography) is associated with mortality in patients with COVID19 [164][165][166] . Arrhythmia in COVID19 also portend higher risk of mortality.…”
Section: F Clinical Consequences Of Cardiac Involvementmentioning
confidence: 99%
“…Li et al reported that despite normal left ventricular ejection fraction values, decreased RV-LS is a strong predictor of mortality in COVID-19 patients [ 17 ]. In another study, it is demonstrated that decreased RV-GLS values were detected to be strong and independent predictor of poor outcomes in patients with COVID-19 [ 18 ]. Baycan et al expressed that decreased RV-GLS is related to in-hospital mortality in COVID-19 cases [ 5 ].…”
Section: Discussionmentioning
confidence: 99%